Role of APP Interactions with Heterotrimeric G Proteins: Physiological Functions and Pathological Consequences - Copenhaver, Philip F.; Kögel, Donat (Frontiers in Molecular Neuroscience, 2017)
Following the discovery that the Amyloid Precursor Protein (APP) is the source of β-amyloid peptides (Aβ) that accumulate in Alzheimer’s disease (AD), structural analyses suggested that the holoprotein resembles a transmembrane receptor. Initial studies using reconstituted membranes demonstrated that APP can directly interact with the heterotrimeric G protein Gαo (but not other G proteins) via an evolutionarily G protein-binding motif in its cytoplasmic domain. Subsequent investigations in cell culture showed that antibodies against the extracellular domain of APP could stimulate Gαo activity, presumably mimicking endogenous APP ligands. In addition, chronically activating wild type APP or overexpressing mutant APP isoforms linked with familial AD (FAD) could provoke Gαο-dependent neurotoxic responses, while biochemical assays using human brain samples suggested that the endogenous APP-Go interactions are perturbed in AD patients. More recently, several G protein-dependent pathways have been implicated in the physiological roles of APP, coupled with evidence that APP interacts both physically and functionally with Gαo in a variety of contexts. Work in insect models has demonstrated that the APP ortholog APPL directly interacts with Gαo in motile neurons, whereby APPL-Gαo signaling regulates the response of migratory neurons to ligands encountered in the developing nervous system. Concurrent studies using cultured mammalian neurons and organotypic hippocampal slice preparations have shown that APP signaling transduces the neuroprotective effects of soluble sAPPα fragments via modulation of the PI3K/Akt pathway, providing a mechanism for integrating the stress and survival responses regulated by APP. Notably, this effect was also inhibited by pertussis toxin, indicating an essential role for Gαo/i proteins. Unexpectedly, C-terminal fragments (CTFs) derived from APP have also been found to interact with Gαs, whereby CTF-Gαs signaling can promote neurite outgrowth via adenylyl cyclase/PKA-dependent pathways. These reports offer the intriguing perspective that G protein switching might modulate APP-dependent responses in a context-dependent manner. In this review, we provide an up-to-date perspective on the model that APP plays variety of roles as an atypical G protein-coupled receptor in both the developing and adult nervous system, and we discuss the hypothesis that disruption of these normal functions might contribute to the progressive neuropathologies that typify AD.